Nilai - Nilai Budaya Madura Yang Berpotensi Mendukung Education For Sustainable Development (ESD) Dalam Meperkuat Ketahanan Sosial Masyarakat - Fathorrozy ,; Mahdi, Akbar; Sa’adah, Nadiatus; Qomariyah, Nurul (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
The concept of Education for Sustainable Development (ESD) emphasizes the importance of integration between social, cultural, and educational aspects in an effort to build a sustainable society. In this study, local cultural values can serve as an important resource that contributes to strengthening social resilience. This research aims to identify and analyze Madura cultural values that have the potential to support the development of ESD in strengthening the social resilience of the community. Through a qualitative approach based on literature studies and cultural analysis, the results of the study show that there are a number of cultural values that have a significant contribution to continuing education practices. (1) the philosophy of Bhuppa', Bhabbhu', Ghuru, Rato which emphasizes the importance of respect for parents, teachers, and leaders as the main foundation in the formation of educational values. (2) the pattern of the Taneyan Lanjhang settlement that strengthens family solidarity and intergenerational learning; (3) a culture of brotherhood in Tretan Dhibi that builds social cohesion; (4) the practice of collective work in Song Osong Lombhung which reflects the economic solidarity of the community; (5) Kobhung's social function as a community learning space and the transmission of religious values. The above cultural values play a role in building social trust, strengthening community networks, and encouraging collective participation in people's lives. With that, the integration of Madura cultural values in the framework of ESD has the potential to strengthen the social resilience of the community and maintain the sustainability of social life at the local level.